Gambaran Tingkat Kecemasan Penderita Diabetes Melitus di Prolanis Puskesmas Cepogo - Salsabilla Az Zahra; Eska Dwi Prajayanti (Pusat Riset dan Inovasi Nasional, 2025)
Diabetes mellitus (DM) is a chronic condition characterized by elevated blood glucose levels due to impaired insulin production or function. This disease is progressive and cannot be fully cured, often causing significant psychological burdens, including anxiety, in sufferers. Anxiety can negatively impact disease management, medication adherence, and the overall quality of life of sufferers. To address this problem, the Chronic Disease Management Program (Prolanis), initiated by BPJS Kesehatan, is one of the Indonesian government's strategic efforts. This comprehensive and sustainable program aims to prevent complications and improve the quality of life of chronic patients, including DM sufferers, through promotive, preventive, curative, and rehabilitative approaches involving a multidisciplinary health team. This study aims to determine the level of anxiety in diabetes mellitus sufferers participating in the Prolanis program at the Cepogo Community Health Center. The approach used was a quantitative descriptive approach with a simple random sampling technique and involved 57 respondents. The results showed that the majority of DM sufferers experienced mild anxiety (54.4%), followed by moderate anxiety (22.8%), severe anxiety (19.3%), and no anxiety (3.5%). Respondents were predominantly middle-aged (82.5%), female (68.4%), and had diabetes for ≤ 5 years (80.7%). Based on these results, it can be concluded that most DM patients in the Prolanis program at the Cepogo Community Health Center experienced mild anxiety, especially in the middle-aged and female groups with a relatively short disease duration. These findings demonstrate the importance of psychological interventions, ongoing education, and emotional support in the care of DM patients to improve their mental resilience and overall quality of life. An active role for healthcare workers in routinely monitoring the psychological aspects of patients is needed to support more effective DM management.